Implikasi Yuridis Penerapan Kode Etik Profesi Advokat Pada Lembaga Bantuan Hukum Di Perguruan Tinggi - Adeffian, Choirul; Nurhikmah, Sri Riski; Priyana, Puti (Morality: Jurnal Ilmu Hukum, 2024)
Legal aid institutions in universities and advocates have a conflict in terms of ethics, both are different entities but have a function as a means of providing legal aid services. Advocates at higher education legal aid institutions have limited space in providing legal aid services with the aim of knowing the regulation of the code of ethics for the advocate profession and its relevance, the regulation of legal aid services and the relevance of its application and the ethical regulations for advocates of legal aid institutions at universities that provide legal aid services. through a normative juridical approach that focuses on literature study. Based on this, it can be explained that advocates at legal aid institutions in higher education actually have limitations in providing legal aid services because they are charged with ethics that regulate them in layers.